Paradoxes of Generational Breaks and Continuity in Jhumpa Lahiri’s The Namesake - Puttaiah, Maharaja College, University of Mysore, India, Venkatesh (Asiatic: IIUM Journal of English Language and Literature, 2012)
Jhumpa Lahiri’s novel The Namesake (2003) shifts its focal point from the first generation of immigrants to the second, in the process establishing interconnectedness of the two generations. While opportunity, movement, displacement and stabilisation form the sequence that defines the lives of the first generation immigrants, the lives of their children, the second generation, revolves around the issues of belonging – whether they belong to the country of their origin or to the country of their birth and whether to adhere to the culture and tradition of their parents or to subscribe to the standards of their immediate world outside home. The article analyses the movement of the two generations of Ganguli family in the United States and the various ways in which they are divided and united in the novel. The focus is on the aspects of cultural variance and assimilation between the two generations.